Nitroxide‐mediated radical polymerization of methacryloisobutyl POSS and its block copolymers with poly(n‐acryloylmorpholine). Issue 3 (10th January 2020) - Ullah, Asad; Shah, Syed M.; Hassan, Abbas; Maric, Milan; Hussain, Hazrat
ABSTRACT: Nitroxide‐mediated radical polymerization (NMP) of the bulky methacryloisobutyl‐polyhedral oligomeric silsesquioxane (POSS‐MA) is successfully achieved after optimizing reaction conditions such as selection of controlling comonomer, comonomer feed molar ratio, and temperature (10 mol % styrene (S) comonomer at 110 °C using the commercially available BlocBuilder as the NMP initiator). The P(POSS‐MA‐ co ‐S) with a molecular weight of 8000 g/mol and dispersity Ð –1.2 is afforded under the optimized reaction conditions. The chain‐end fidelity is verified by chain extension experiments with N‐ acryloyl morpholine (ACM) via NMP that produces well‐defined amphiphilic hybrid P(POSS‐MA‐ co ‐S)‐ b ‐P(ACM) x block copolymers, where the subscript " x " represents the degree of polymerization of (ACM) block (182 < x < 695). The size exclusion chromatography (SEC) of the as‐synthesized samples reveals the presence of some dead P(POSS‐MA‐ co ‐S) chains that could be removed by a simple purification step. Kinetic investigations reveal a first‐order kinetics for the polymerization of ACM using P(POSS‐MA‐ co ‐S) as the macroinitiator under NMP conditions. The kinetic and SEC data confirms the controlled nature of the NMP of ACM. Being amphiphilic, the formed P(POSS‐MA‐ co ‐S)‐ b ‐P(ACM) x block copolymers self‐assembled in aqueous solution as revealed by the fluorescence spectroscopy experiments with pyrene as the probe for determination of the critical micelle concentration and dynamic light scattering studies. © 2020 Wiley Periodicals, Inc. J. Polym. Sci. 2020, 58, 428–437 Abstract : Nitroxide‐mediated radical polymerization (NMP) of the bulky methacryloisobutyl POSS (POSS‐MA) is successfully achieved after optimizing reaction conditions such as selection of the controlling comonomer, comonomer feed molar ratio, and temperature. The chain‐end fidelity is verified by chain extension experiments with N‐ acryloyl morpholine (ACM) via NMP that produces well‐defined amphiphilic hybrid P(POSS‐MA‐ co ‐S)‐ b ‐P(ACM).